Fintech Aplikasi Jaklingko Dalam Bisnis Transportasi Umum Dan Kaitannya Dengan Inovasi Terbuka - Eny Purwaningsih; Dita Wahyu Saputra; Ickhsanto Wahyudi; Barlia Annis Syahzuni (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
The advancement of digital technology has changed the paradigm in various sectors, including the financial industry with the emergence of Financial Technology (FinTech). In Indonesia, the growth of urbanization and private vehicle ownership in Jakarta has caused serious problems in the urban transportation system. Especially related to congestion, requiring new innovations such as digital payments as a solution. This study investigates the factors that influence the adoption of FinTech services through the JakLingko application, in the context of public transportation in DKI Jakarta, involving 185 respondents. Using a quantitative approach and SEM-PLS with SmartPLS software for testing. Based on the updated UTAUT2 theory, variables such as Performance Expectancy, Effort Expectancy, Facilitation Condition, Price Value, and Knowledge are proven to have a significant influence on Fintech Adoption. While variables such as Social Influence, Hedonic Motivation, Habit, and Perceived Security do not show a significant influence. In addition, Fintech Adoption affects the Business Sustainability of public transportation. These results provide in-depth insight into the dynamics of FinTech technology adoption in the public transportation sector. The implication of these findings is the importance of the government and transportation service providers understanding these factors to improve operational efficiency and user experience in the use of digital payments in the public transportation sector, thereby supporting Business Sustainability and improving transportation services in Jakarta.